Managing Traditional ‘Cat and Mouse’ Play to Optimize Gross Motor Development in Early Childhood - Larasati, Sekar Ayu; Sit, Masganti (Al-Qalam Institue, 2025)
This study aimed to enhance young children’s gross motor skills through the traditional “Cat and Mouse” game, which fosters agility, balance, speed, and coordination. Adopting the Kemmis and McTaggart Classroom Action Research model, the intervention was implemented over two cycles with 18 participants (8 girls and 10 boys). Data were gathered through structured observation and systematic note-taking. Results demonstrated marked improvement in gross motor performance, increasing from 44% before the intervention to 66% in the first cycle and 88% in the second cycle. These findings highlight the effectiveness of traditional games as pedagogical tools for physical development in early childhood. From a management perspective, incorporating culturally rooted, low-cost, and easily organized activities into curriculum planning not only enhances developmental outcomes but also improves efficiency in program implementation, resource allocation, and engagement strategies. This approach offers an adaptable model for educators and administrators seeking to balance developmental objectives with practical management considerations.